EFFICACY OF HOMOEOPATHIC MEDICNES IN THE TREATMENT OF IRON DEFICIENCY ANAEMIA OF FEMALES WITH CONSTITUTIONAL APPROACH - CASE REPORT - Dr. M. Prakash Kumar; Dr. Ketan Shah; Dr. Poorav Desai; Dr. H.P. Namratha (The Bioscan, 2025)
Anaemia is a serious public health problem, which affects the mental and physical development, as well as health maintenance and work performance. Iron deficiency is by far the most common cause of anaemia worldwide. About 2 billion people are suffering from varying degrees of anaemia in developing countries. The cases of iron deficiency anaemia are commonly found in day to day (routine) practice. A case of 34 years old female suffering from iron deficiency anaemia reported in the clinic was treated successfully within 5 months by individualised homoeopathic medicine Arsenicum Album 200 with repetition as per requirement. The evidence of improvement was reduced breathlessness and increased serum haemoglobin level.